The Evolution of Active Learning Research in Primary Education Over a Decade: A Bibliometric Analysis of Trends, Stagnation, and Academic Collaboration (Musamus Journal of Primary Education)
Research on active learning in primary education has grown significantly over the past decade but has experienced stagnation in publications and limited academic collaboration. This study aims to analyze active learning research trends, identify the factors contributing to stagnation, and examine global academic collaboration patterns using bibliometric analysis. Data were retrieved from Scopus, comprising 67 documents published between 2014 and 2025, and analyzed using RStudio (Biblioshiny) to identify publication trends, collaboration networks, and keyword relationships. The results indicate a decline in publication growth (-2.58% per year) due to a research shift toward technology-based learning approaches, such as artificial intelligence and gamification. Academic collaboration remains low (14.93%), with developed countries like the United States and the United Kingdom dominating, while researchers from developing countries face limited access to global scholarly networks. This study highlights the need to integrate active learning with digital innovations and enhance academic collaboration through research grants and open-access publications. These findings provide valuable insights for academics and policymakers to strengthen active learning research at the global level.